(untitled) (Journal of Artificial Intelligence & Research, 2023)
The integration of Artificial Intelligence (AI) in telematics systems represents a significant advancement in the realm of real-time driver behaviour analysis and accident prevention. This research explores the transformative potential of AI-enhanced telematics systems in modern vehicles, focusing on their capability to process vast amounts of real-time data to monitor and analyze driver behaviour, detect hazardous driving patterns, and implement predictive safety measures to mitigate road accidents. Telematics systems, traditionally employed for vehicle tracking and diagnostics, have evolved with the incorporation of AI algorithms to offer comprehensive insights into driver behaviour. By leveraging data collected from in-vehicle sensors, GPS systems, and on-board diagnostics, AI algorithms can identify and interpret patterns indicative of risky driving behaviours such as excessive speeding, erratic lane changes, and sudden braking. These systems utilize advanced machine learning techniques, including supervised and unsupervised learning, to refine their predictive models and enhance their ability to forecast potential accident scenarios. The research emphasizes the role of AI in enhancing the efficacy of real-time alerts and interventions. Through continuous monitoring of driver actions and contextual factors such as road conditions and traffic density, AI systems can generate immediate warnings to drivers about dangerous behaviours and provide actionable feedback to improve driving habits. Additionally, the analysis highlights the use of AI for the development of adaptive safety systems that not only respond to immediate threats but also offer long-term behavioural improvements through personalized coaching and feedback. A critical aspect of this study involves the examination of predictive safety measures enabled by AI-enhanced telematics. Predictive models, powered by AI, analyze historical and real-time data to assess the likelihood of potential accidents and hazardous situations. These models employ techniques such as predictive analytics and anomaly detection to anticipate risky events before they occur, allowing for timely interventions that can prevent accidents. The research also discusses the integration of AI with vehicle-to-everything (V2X) communication systems, which facilitate the exchange of information between vehicles, infrastructure, and other road users, further enhancing the accuracy and effectiveness of predictive safety measures. Furthermore, the paper explores the challenges and limitations associated with the deployment of AI-enhanced telematics systems. Issues such as data privacy, the need for robust data security protocols, and the ethical implications of continuous monitoring are critically analyzed. The study also addresses the technical challenges related to the real-time processing of large volumes of data and the need for scalable infrastructure to support AI algorithms. Case studies of real-world implementations demonstrate the practical benefits of AI-enhanced telematics systems in reducing road accidents and improving overall road safety. These case studies highlight the success of various AI-driven initiatives in different regions, showcasing how the integration of advanced telematics technology has led to significant reductions in accident rates and improvements in driver behavior.